Strategies used by families to care for hospitalized child - Giovana Calcagno Gomes; Fernanda Lucas Lopes de Meirelles Leite; Nathalia Zinn de Souza; Daiani Modernel Xavier; Joana Curcio da Cunha; Daniela Pasini (Universidade Federal de Goias, 2014)
This study seeks to investigate the strategies used by families to care for a hospitalized child. A qualitative study with methodological references based on the Grounded Theory. It was conducted in a pediatric ward in a hospital in southern Brazil. Participants comprised 18 families caring for children admitted in the first semester of 2010 divided in four sample groups. Data was collected using semi-structured interviews. Simultaneously, we conducted an open and axial data analysis. The data displayed that families use strategies such as seeking out information about treatment; reproducing home care in the hospital; organizing the care environment and becoming familiar with care technology. We concluded that by implementing care strategies for the hospitalized child, the family becomes co-participants in the hospitalization process, humanizing the hospital environment, and thus providing the child with qualified, sensitive and humane care. doi: 10.5216/ree.v16i2.21112.